Challenging assumptions: “unveiling meritocracy’s reality in neurosurgery” - Encarnacion Ramirez, Manuel De Jesus; Peralta Baez, Ismael Antonio; Reyes Soto, Gervith; Ntalaja Mukengeshay, Jeff; tshiunza, Cherubin mpoyi; Rosario, Andreina Rosario; Vladimir Nikolaevich, Nikolenko; Nurmukhametov, Renat; Kannan, Siddarth; Simfukwe, Keith; Duchén Rodríguez, Luis Miguel; Chmutin, Gennady; et al. (Frontiers in Surgery, 2024)
Introduction: Meritocracy, a concept revered as the cornerstone of fairness and equal opportunity, is critically examined in the context of neurosurgery. This article challenges the notion that success in this demanding field is solely determined by individual abilities and effort. By investigating how these systemic barriers impact admissions to neurosurgical training programs and professional advancement, the paper underscores the complexity of meritocracy in neurosurgery, suggesting that the meritocratic ideal is more nuanced and influenced by external variables than commonly believed. Results: Certain universities deemed elite offer a curriculum divergent from that of their counterparts in low and middle-income countries. Students at these "elite" institutions gain exposure to new technologies and research incentives, which brings us to the realm of research. Remarkably, 75% of articles originating from developed nations account for just 25% of traumatic brain injury cases. This disparity highlights a significant research imbalance, and the common refrain underscores the need to bolster research capabilities in low-income countries. Neurosurgeons in the United States receive a median? salary of $412,000 dollars per year, compared to $13200 dollars in Latin America, as of June 2023. Given such incongruities, the prospect of even attending conferences or workshops abroad remains difficult for neurosurgeons from developing nations. Research isn't cast aside due to a lack of interest but due to resource. The narrative promotes a collective endeavour to dismantle barriers and embrace innovation, emphasizing the importance of mentorship, cross-institutional collaboration, and the amplification of underrepresented voices.